TEACHING GRAMMAR THROUGH STORY-BASED INTEGRATIVE METHOD - Sharipova Firuza Mehriddinovna (Modern American Journals, 2025)
The present article examines a story-based integrative method for teaching grammar in English lessons, aimed at developing both grammatical and speech competence among 6th-grade students. Traditional approaches to teaching grammar in isolation often fail to ensure effective application in real communicative situations. The proposed method presents grammatical units, such as personal pronouns (I, you, he, she, it, we, they) and the present forms of the verb to be (am, is, are), as story characters, allowing students to perceive grammar as meaningful and functional elements of language. The article describes the theoretical and methodological foundations of the author’s approach and presents an integrative system of exercises, including dialogue, question-and-answer tasks, role-playing, and rhythmic repetition. The method fosters active speech participation, enhances long-term retention of grammatical knowledge, and increases students’ motivation in lessons.
Keywords: Story-based learning, integrative grammar teaching, speech competence, personal pronoun, verb to be, communicative approach, 6th-grade English learners